Methods of Individual Creativity Stimulation - Rusu Marinela (Sciendo, 2019)
Creativity is one of the specific human traits. The development of personality is most often realized in close correlation with the creative dynamics of each one. The paper proposed by us brings into discussion the most important factors that contribute to the development of creativity. What makes us more creative, what are the conditions that unleash the creative forces of the individual's mind? First, the cultural factors, inherited ideas about creativity, are critically analyzed. Thus, there are a number of "myths of creativity" that infuse our perception (sometimes in a wrong way) on the definition and understanding of creativity. The family also offers, through education and personal example, means of stimulating creativity. It is the first step towards performance creativity. In this paper, we also present the best-known techniques of creativity training, some of them, in the view of the "new age" trend. Creativity always interferes with a task, as we have to improvise, responding for moment to moment to the changing demands of the situation. Daily creativity improvise and is therefore, different from what the researchers of creativity have studied: creativity that results in a finished product. In order to become more creative, we will have to orient ourselves differently: to have a motivation for it, to choose a field in which we excel, to accept collaboration, to be confident and take risks. Creativity means rejecting the conventional, the routine and finding new solutions in personal development.